Sejarah perkembangan pesantren sebagai lembaga pendidikan islam di Indonesia - Ridho Hafiezd Maulana; Abdul Rasyid; Muhammad Syamsul Munir (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Pesantren are the oldest Islamic educational institutions in Indonesia and play a vital role in spreading Islamic teachings, shaping the character of society, and advancing religious education throughout the archipelago. Pesantren serve not only as places to study religious knowledge but also as social institutions that contribute to societal progress. The objectives of this study are to examine the history of the establishment of pesantren in Indonesia, analyze their development at various points in history, explain their function within the national Islamic education system, and identify how pesantren have adapted to modernization and technological advancements. This study adopts a qualitative approach using historical research methods through a literature review. Data were collected from various primary sources, such as historical documents and archives, as well as secondary sources, including books, scholarly articles, and previous studies, which were analyzed using data reduction, data presentation, and conclusion-drawing methods. Research findings indicate that pesantren have evolved since the arrival of Islam in the Indonesian archipelago and have undergone changes in line with social and political dynamics, as well as national education policies. During the colonial period, pesantren served as centers of Islamic education as well as bases for the struggle against colonialism. After Indonesia gained independence, pesantren began to adapt to the national education system through improvements to their curriculum and organizational structure. In the modern era, pesantren have successfully transformed by integrating religious studies with general education, utilizing digital technology in the learning process, and strengthening their role in empowering communities without neglecting Islamic values. Thus, pesantren remain adaptive and relevant Islamic educational institutions that play a significant role in the development of Indonesia’s human resources. Pesantren adalah institusi pendidikan Islam tertua yang ada di Indonesia, memainkan peran penting dalam menyebarluaskan Islam, membentuk karakter masyarakat, serta memajukan pendidikan keislaman di berbagai daerah di Nusantara. Keberadaan pesantren tidak hanya berfungsi sebagai ruang untuk mentransfer pengetahuan agama, tetapi juga sebagai lembaga sosial yang berkontribusi dalam pembangunan komunitas. Studi ini bertujuan untuk meneliti sejarah lahirnya pesantren di Indonesia, menganalisis perkembangan pesantren di berbagai era sejarah, menjelaskan peran pesantren di dalam sistem pendidikan Islam nasional, serta mengidentifikasi cara adaptasi pesantren terhadap modernisasi dan kemajuan teknologi. Penelitian ini menggunakan metode kualitatif dengan pendekatan penelitian sejarah melalui kajian literatur. Data dikumpulkan dari beragam sumber primer seperti dokumen sejarah dan arsip, serta sumber sekunder meliputi buku, artikel ilmiah, dan penelitian sebelumnya yang dianalisis dengan teknik reduksi data, penyajian data, dan penarikan kesimpulan. Temuan penelitian menunjukkan bahwa pesantren telah berkembang sejak kedatangan Islam ke Nusantara dan mengalami perubahan sejalan dengan dinamika sosial, politik, serta kebijakan pendidikan nasional. Pada masa penjajahan, pesantren menjadi pusat pendidikan Islam sekaligus basis perjuangan melawan kolonialisme. Setelah Indonesia merdeka, pesantren mulai beradaptasi ke dalam sistem pendidikan nasional melalui perbaikan kurikulum dan organisasi. Di zaman modern, pesantren mampu bertransformasi dengan menggabungkan ilmu agama dengan ilmu umum, memanfaatkan teknologi digital dalam proses pembelajaran, dan memperkuat perannya dalam memberdayakan masyarakat tanpa mengesampingkan nilai-nilai keislaman. Dengan demikian, pesantren tetap menjadi lembaga pendidikan Islam yang adaptif, relevan, dan memiliki peranan signifikan dalam pembangunan sumber daya manusia Indonesia.